Effects of Kaolin particle size and annealing temperature on the Resistivity of Zinc- Kaolin Composite Resistors - OA Babalola; T Akomolafe (Journal of Applied Sciences and Environmental Management, 2010)
The effects of kaolin particle sizes on the resistivity of zinc-kaolin composite resistors have been investigated. The composite resistors have been produced from kaolin particle sizes ranging from 0.063 mm to 0.5 mm. The resistors were produced in a mould to a dimension of 65 mm x 6.5 mm x 3.2 mm with dry zinc and kaolin powders to which a drop or two of sodium silicate have been added as a binder. The resistors were annealed at temperatures ranging from 300 oC to 1000 oC in steps of 100 oC for composites of 0%, 5%, 40% and 60%(vol.) zinc content. Results showed that composite resistivity at all the zinc concentrations considered and at all annealing temperatures increased exponentially with increasing kaolin particle size. The effect of annealing showed that composite resistance is highest for composites annealed at 1000 oC and lowest for cermets annealed between 500 oC and 600 oC. Composite resistance increased with increasing kaolin particle size due to the large contact area presented by the insulating kaolin particles resulting in reduction of the number of zinc particle-particle contact. The results from this study will help in the development of conducting ceramics which could find use in chemical industries as electrodes in environments not conducive for metallic electrodes.